Interactional Styles Used by Lucinta Luna In Episode 1 #TheFamily YouTube Series - Christine Novita (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study aims to examine the feminine interactional styles and masculine interactional styles used by Lucinta Luna in the YouTube video Terbongkar: Lucinta Keceplosan Alasan Ayu Ting Ting Tolak Boy! Episode 1 #TheFamily. Besides, the writer employed a qualitative approach using Holmes’ (2006) theory on feminine interactional styles and masculine interactional styles.Moreover, the writer collected all utterances of Lucinta Luna in her interaction with the host and the participants. The analysis presented Lucinta utilized both feminine and masculine interactional styles, but she used more feminine interactional styles. Nonetheless, she did not use one feature of masculine interactional style at all, which is aggressive interruptions. She used more feminine language, which was related to her gender as a trans woman.